Discovery and characterisation of anti-amyloid beta fibril antibodies from naive phage display VHH libraries - Fernandez Bonfante, Juan (2022)
Parkinson’s disease (PD) and Alzheimer’s disease (AD) are two of the most common incurable neurological disorders affecting the worldwide population over 60 years of age and are characterized by the progressive loss of either motor or cognitive functions in affected individuals. Although the main cause of these diseases remains unknown, genetic, histological and animal models point to the progressive accumulation of misfolded synaptic proteins called alpha-synuclein (α-syn) and amyloid beta (Aβ) as the main suspects in, respectively, causing PD or AD. In pathological conditions, α-syn and Aβ have been observed to change their physiological conformations and aggregate into protein polymers, also known as fibrils. These different structures have been directly linked to disease progression, and thus the in depth understanding of these polymers is crucial for future hopes of identifying a cure for PD or AD. Currently, no drugs have been identified with the ability to reverse or reduce the disease burden of these diseases, with available therapies only delaying the inevitable progression of the diseases. During this project, a way to reproduce these disease-relevant structures was identified through the means of protein misfolding cyclic amplification (PMCA) and real-time quaking induced conversion (RT-QUIC), two methodologies developed for the amplification of protein polymers in vitro. By means of different biochemical and imaging methods two distinct α-syn polymorphs and two Aβ conformers were detected. Next, a naïve VHH library was implemented to discover antibodies against the characterized Aβ fibrils through several rounds of biopanning. This was done for both full-length fibril conformers (or polymorphs) and fragmented fibrils, with the latter strategy targeting the elongation sites responsible for fibril propagation. Overall, an array of antibodies were discovered that bound to fibrils or fragmented fibrils. The binding properties of these antibodies were then characterized through immunoassays and the measuring of biomolecular interactions with bio-layer interferometry. This was achieved using both fibril polymorphs, fragmented fibrils, monomers (sourced from one supplier, Genscript) and a mixed solution of monomers, oligomers and protofibrils sourced from another supplier (Gencust). From this analysis it was revealed that fibril binders could be grouped in three categories, depending on their binding affinity to each of the different Aβ forms tested: 1) binders to all forms tested (including fibrils, monomers, oligomers and protofibrils); 2) binders to both fibril polymorphs and the mixed aggregate solution from Gencust and 3) binders to a single fibril polymorph and Gencust monomers, oligomers and protofibrils. Fragmented fibril binders, on the other hand, could be grouped in 4 categories: 1) binders to fragmented fibrils, both fibril conformers and Gencust monomers, oligomers and protofibrils; 2) binders to fragmented fibrils, one of the fibril polymorphs and Gencust monomers, oligomers and protofibrils; 3) binders to a single fibril polymorph and Gencust monomers, oligomers and protofibrils and 4) binders to all forms of Aβ tested (including fragmented and both full-length fibril polymorphs, Genscript monomers and Gencust monomers, oligomers and protofibrils). Functional assays were then attempted for 9 antibodies, producing preliminary data demonstrating that the VHH antibodies identified through phage display might have a protective effect in vitro with the inhibition of the formation of fibrils in solution.